Determination and Evaluation of Field Adequacy by Ankara Göksu Park Users - Elif Nur Doğan; Sertaç Güngör (Turkish Journal of Agriculture: Food Science and Technology)
It is one of the biggest city parks of Ankara, which people can easily reach in daily use, walking, jogging, sitting, picnicking, playing etc. Göksu Park, which provides opportunities for activities such as, is built on the old Susuz pond in Eryaman. The park was opened in 2003. In this study, a 3-stage method was applied to determine and evaluate the area adequacy of the park. In the first stage, the first picture selection was made with the team of landscape architects in the park, using the nominal group technique, among the photographs taken in the area, obtained from the municipality and received the most likes from social media accounts with many followers. In the second stage, the criteria for the evaluation of field adequacy with the Delphi technique were determined by consulting the faculty members in the Department of Landscape Architecture, Faculty of Agriculture, Ankara University, who were selected as experts on the subject. Then, using the observation and comparison tables, the survey questions were prepared and after the application of the survey to the visitor group and park staff, as the third step, the survey data was based on whether the difference between the observed frequencies (OF) and expected frequencies (EF) was statistically significant with the help of SPSS 25 statistical program. Chi-square independence analysis, which is a test, and linear regression analysis were performed. By counting the frequencies, the relevant photographs will be examined and the relationship between density and field adequacy has been interpreted. With this study, it will contribute to the plans and designs of new projects so that the green areas and parks that people need due to the increasing population and urbanization can be used adequately in the future.